Function and Structural Organization of the Replication Protein of Bamboo mosaic virus - Meng, Menghsiao; Lee, Cheng-Cheng (Frontiers in Microbiology, 2017)
The genus Potexvirus is one of the eight genera belonging to the family Alphaflexiviridae according to the Virus Taxonomy 2015 released by International Committee on Taxonomy of Viruses (www.ictvonline.org/index.asp). Currently, the genus contains 35 known species including many agricultural important viruses, e.g. Potato virus X (PVX). Members of this genus are characterized by flexuous, filamentous virions of 13 nm in diameter and 470–580 nm in length. A potexvirus has a monopartite positive-strand RNA genome, encoding five open-reading frames (ORFs), with a cap structure at the 5’ end and a poly(A) tail at the 3’ end. Besides PVX, Bamboo mosaic virus (BaMV) is another potexvirus that has received intensive attention due to the wealth of knowledge on the molecular biology of the virus. In this review, we discuss the enzymatic activities associated with each of the functional domains of the BaMV replication protein, a 155-kDa polypeptide encoded by ORF1. The unique cap formation mechanism, which may be conserved across the alphavirus superfamily, is particularly addressed. The recently identified interactions between the replication protein and the plant host factors are also described.